EFFECT OF FLUORIDE SOLUTION ON SALIVARY AMYLASE ACTIVITY - Willianti, Enny (Universitas Wijaya Kusuma Surabaya, 2015)
Fluoride has the benefit on the tooth to inhibit caries. Fluoride is systemically incorporated into the crystal lattice of enamel by exchanging positions with the hydroxyl ion to result in formation of fluorapatite. Fluoride used locally may inhibit tooth demineralization, one of the mechanism is that fluoride is suspected to inhibit salivary amylase activity.The aim of this research is to exam whether fluoride inhibits salivary amylase activity and at what concentration.Method of this research was experimental research and the design was